The Role of Management and Industry 5.0 Technology on Generation Z Productivity in Medan City - Safira, Alya Diva; Rizky, M. Chaerul; Muftiha, Keisa Adisti; Tambunan, Lufthi Nanda Syahputra; Safina, Putri (Research Horizon, 2025)
The rapid digital transformation ushered in by Industry 5.0 has redefined human-technology interactions, emphasizing collaboration between artificial intelligence and human capabilities, particularly among Generation Z, who are digital natives with advanced technological proficiency and expectations for personalized services. This study aims to examine the influence of digital-based management and Industry 5.0 technology on the characteristics and productivity of Generation Z in Medan, a key economic hub in North Sumatra. A quantitative approach was employed, involving questionnaires distributed to 44 respondents aged 18–24 years, with data analyzed through Pearson correlation, reliability testing, coefficient of determination, and hypothesis testing. The findings reveal that Industry 5.0 technology exerts a dominant influence on Generation Z, with a strong correlation of 0.775 and a high significance level, while management also has a significant positive effect, with a correlation of 0.622. Approximately 63.5% of the variation in Generation Z’s characteristics is explained by these variables. The study concludes that integrating adaptive management with Industry 5.0 technologies is essential to optimize Generation Z’s potential, enabling organizations to foster innovation and productivity in a digital era.